Еlectrodes dimensions effect on the self-sustained plasma-beam discharge power - Hrechko, Ya.O.; Azarenkov, N.A.; Babenko, Ie.V.; Ryabchikov, D.L.; Sereda, I.N.; Boloto, D.A.; Tseluyko, A.F. (Вопросы атомной науки и техники, 2018)
The possibility of increasing the active power inputted into the discharge is shown by reducing the working surface area of the high-voltage electrode in high-current pulsed plasma diode of low-pressure. Under conditions of double electric layer formation, the power densities up to 2 GW/cm² are achieved in the discharge at initial stored energy up to 200 J.